ABO-Incompatible Adult Living Donor Liver Transplantation in the Era of Rituximab: A Systematic Review and Meta-Analysis - Dipesh Kumar Yadav; Yong Fei Hua; Xueli Bai; Jianying Lou; Risheng Que; Shunling Gao; Yun Zhang; Ji Wang; Qinfen Xie; Muhammad Ibrahim Alhadi Edoo; Vikram Kumar Chutturghoon; Tingbo Liang (Gastroenterology Research and Practice)
Aim. The primary aim of this study is to compare the short- and long-term outcomes between ABO-incompatible (ABOi) adult living donor liver transplantation (ALDLT) with rituximab prophylaxis and ABO-compatible (ABOc) ALDLT. Background. The strategy of ABOi liver transplantation (LT) was originated initially to increase the donor pool and to enable liver transplantation in emergency conditions. However, ABOi ALDLT remains a controversial approach in comparison to ABOc ALDLT. Methods. PubMed, Embase, and the Cochrane Library study search were accomplished to recognize studies comparing ABOi and ABOc ALDLT. Meta-analyses were conducted based on the evaluation of heterogeneity using a fixed-effect model and a random-effect model to assess the short- and long-term outcomes following ABOi ALDLT with rituximab prophylaxis. Results. Nine studies comprising a total of 3,922 patients (ABOi=671 and ABOc=3,251) were identified. There was no significant difference between ABOi and ABOc groups for 1-year, 3-year, and 5-year OS and graft survival, respectively. Moreover, 1-year and 3-year OS and DFS were similar between both groups for HCC patients. However, ABOi ALDLT had higher incidences of CMV infection, AMR, overall biliary complications, and biliary stricture than ABOc ALDLT and had other comparable postoperative complications. Conclusion. Our meta-analysis included studies comparing ABOi and ABOc ALDLT after the introduction of rituximab in a desensitization protocol for ABOi ALDLT. The results of ABOi ALDLT were comparable with those of ABOc ALDLT. However, biliary complications, CMV infection, and AMR remain a concern in the era of rituximab.